2019
DOI: 10.3126/bjhs.v4i1.23940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thrombocytopenia and Mortality in Critically ill Children Admitted to PICU in Tertiary Hospital In Biratnagar

Abstract: Introduction: Thrombocytopenia is a clinical condition characterized by decrease in number of platelets below the normal range. It is associated with bleeding tendency, hemodynamic instability, impaired inflammatory process and thus affecting host defence mechanism. There has been only few studies published till date in pediatric intensive care units suggesting thrombocytopenia is associated with increased mortality. Objectives: To determine the prevalence of thrombocytopenia in the critically ill childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
4
2
0
Order By: Relevance
“…This was in accordance with Venkata et al, [22], who found that thrombocytopenia carries an independent risk for mortality in ICU patients and is a negative prognostic indicator for adverse clinical outcomes in ICU patients [22]. Also, a recent study stated that thrombocytopenic children at the time of admission have more likelihood of mortality than non-thrombocytopenic children in intensive care units [23]. Gao et al, [24] found that PCT was correlated to platelet count with similar clinical implication, and they found markedly decreased PCT in patients who expired.…”
Section: Discussionsupporting
confidence: 88%
“…This was in accordance with Venkata et al, [22], who found that thrombocytopenia carries an independent risk for mortality in ICU patients and is a negative prognostic indicator for adverse clinical outcomes in ICU patients [22]. Also, a recent study stated that thrombocytopenic children at the time of admission have more likelihood of mortality than non-thrombocytopenic children in intensive care units [23]. Gao et al, [24] found that PCT was correlated to platelet count with similar clinical implication, and they found markedly decreased PCT in patients who expired.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the prevalence was 37.78%. This is similar to the results shown in the studies conducted by Sah et al [15] and Kaur et al [1] where the prevalence of thrombocytopaenia was 34% and 32.36%, respectively. Relatively higher prevalence was observed in the studies conducted by Divecha et al [8] (60.3%), Yilmaz et al [6] (59.57%) and Mussa et al [16] (44.61%), respectively, while relatively lower prevalence was observed in the studies conducted by Krishnan et al [17] (25.3%) and Agrawal et al [7] (25%).…”
Section: Prevalencesupporting
confidence: 92%
“…In this study, maximum patients 24 out of total 68 thrombocytopaenic patients that is, 35.29% had mild thrombocytopaenia followed in decreasing order by moderate thrombocytopaenia (33.82%), severe thrombocytopaenia (19.12%) and very severe thrombocytopaenia (11.76%). Similar results were observed in the study conducted by Sah et al [15] where maximum (41.7%) patients had mild thrombocytopaenia (platelet count <150 × 10 9 /L) followed by 32.3% of patients with moderate thrombocytopaenia (platelet count <100 × 10 9 /L) and 26.4% of patients with severe thrombocytopaenia (platelet count <50 × 10 9 /L). Studies conducted by Mundkur et al [18] and Kaur et al [1] who showed higher prevalence of severe thrombocytopaenia 51% (platelet count <50 × 10 9 /L) whereas the study by Yilmaz et al [6] showed lower prevalence (7.45%) of severe thrombocytopaenia as compared to our study.…”
Section: Severity Of Thrombocytopaeniasupporting
confidence: 90%
See 2 more Smart Citations